Therapeutic roles of thiazides and loop diuretics in blood pressure control and renal protection against chronic kidney disease - Wonji Jo; Eun Sil Koh; Sungjin Chung (BMC, 2023)
Abstract Fluid overload secondary to loss of functional nephron mass can elevate blood pressure, which is characteristic of hypertension shown in chronic kidney disease (CKD). Therefore, it is logical to use diuretics at appropriate dose to lower blood pressure in patients with CKD and hypertension. Despite the theoretical background on the use of diuretics in CKD, there have been no definitive data on the effectiveness or safety of diuretics as first-line therapy for the management of hypertension in patients with CKD. Results from some clinical trials have demonstrated that diuretics would not lower blood pressure. They could even worsen electrolyte imbalance and kidney function when they are administered in patients with CKD. Major clinical practice guidelines on management of blood pressure or CKD have stated that evidence for benefits of thiazide diuretics is not conclusive yet in patients with advanced CKD, although loop diuretics are often effective for volume control at lower glomerular filtration rate. Recently, evidence for diuretics as effective blood pressure lowering agents in patients with advanced CKD is increasing. Renoprotective effect of thiazide or loop diuretics might represent a consequence of their influence on blood pressure or their ability to potentiate the effect of renin-angiotensin system blockade by making intraglomerular pressure more renin-angiotensin system-dependent, although their direct benefit on renal function remains controversial. This review summarizes recent data on the possible role of diuretics in lowering blood pressure, slowing the progression of kidney disease, and reducing cardiovascular risk in CKD patients.